Is Anopheles gambiae a Natural Host of Wolbachia? - Ewa Chrostek (American Society for Microbiology, 2019)
ABSTRACT Wolbachia (Alphaproteobacteria, Rickettsiales) is an intraovarially transmitted symbiont of insects able to exert striking phenotypes, including reproductive manipulations and pathogen blocking. These phenotypes make Wolbachia a promising tool to combat mosquito-borne diseases. Although Wolbachia is present in the majority of terrestrial arthropods, including many disease vectors, it was considered absent from Anopheles gambiae mosquitos, the main vectors of malaria in sub-Saharan Africa. In 2014, Wolbachia sequences were detected in A. gambiae samples collected in Burkina Faso. Subsequently, similar evidence came from collections all over Africa, revealing a high Wolbachia 16S rRNA sequence diversity, low abundance, and a lack of congruence between host and symbiont phylogenies. Here, we reanalyze and discuss recent evidence on the presence of Wolbachia sequences in A. gambiae. We find that although detected at increasing frequencies, the unusual properties of these Wolbachia sequences render them insufficient to diagnose natural infections in A. gambiae. Future studies should focus on uncovering the origin of Wolbachia sequence variants in Anopheles and seeking sequence-independent evidence for this new symbiosis. Understanding the ecology of Anopheles mosquitos and their interactions with Wolbachia will be key in designing successful, integrative approaches to limit malaria spread. Although the prospect of using Wolbachia to fight malaria is intriguing, the newly discovered strains do not bring it closer to realization. IMPORTANCE Anopheles gambiae mosquitos are the main vectors of malaria, threatening around half of the world’s population. The bacterial symbiont Wolbachia can interfere with disease transmission by other important insect vectors, but until recently, it was thought to be absent from natural A. gambiae populations. Here, we critically analyze the genomic, metagenomic, PCR, imaging, and phenotypic data presented in support of the presence of natural Wolbachia infections in A. gambiae. We find that they are insufficient to diagnose Wolbachia infections and argue for the need of obtaining robust data confirming basic Wolbachia characteristics in this system. Determining the Wolbachia infection status of Anopheles is critical due to its potential to influence Anopheles population structure and Plasmodium transmission.